Analisis Pengaruh Return on Assets, Pertumbuhan Laba dan Leverage terhadap Return Saham (Studi Kasus Pada Industri Property yang terdaftar di Bursa Efek Indonesia) - Harry Barli (Universitas Pamulang, 2016)
Return allows investors to compare the actual profits and gains expected by a wide range of investments in the required return. On the other hand, the return has a very significant role in determining the value of a invetasinya. This study aims to provide evidence that stock returns are affected by Return on Assets, Income Growth and Leverage. Data taken from the Indonesia Stock Exchange on the industrial property sector in 2013-2014 were processed using SPSS version 22 to test the hypothesis with multiple regression analysis. With the results of research Return On Asset positive and significant impact on Return stocks, while profit growth and leverage in this study had no effect on Stock Return, but simultaneously Return On Asset, Income Growth and Leverage effect on Stock Return